Revalidation of the global health questionnaire-12: factor analysis and demographic correlation - Ratnapuri, Adisti; Zubaidah, Siti; Mahanal, Susriyati; Susanto, Hendra; Setiyowati, Arbin Janu; Saefi, Muhammad (International Journal of Public Health Science (IJPHS), 2025)
Global health questionnaire-12 (GHQ12) is the most common instrument used to measure mental health. However, the factor structure of the GHQ12 has not been fully explored. This study aims to assess the factorial structure of the GHQ12 and explore demographic factors associated with mental wellbeing in a population of prospective biology teachers in Indonesia. This cross-sectional survey was conducted for two weeks in July 2023 by recruiting 1186 students who were predominantly female (85.92%), over 20 years old (68.79%), only studying without working (90.47%), and third year (33.81%). Exploratory factor analysis (EFA) and confirmatory factor analysis (CFA) were used to extract and assess the suitability of the resulting models. GHQ12 scores were also reviewed concerning demographic characteristics using comparison tests. Two factors including depression and social dysfunction accounted for 58.78% of the variance. This two-factor model was confirmed to fit the actual data. Additionally, we found differences between men and women on both factors and total scores. In addition, there are differences between students who only study and those who work on depression factors. This study suggests that the factor structure of the GHQ12 is a valid and reliable measurement for evaluating the mental health of prospective biology teachers.